Women Between Jail: A Discourse of Women Protection on Indonesia Correctional Act - Chuldun, Ibnu; Rokhman, Fathur; Widiyanto, Widiyanto (Universitas Negeri Semarang, 2024)
This paper explores the intersection of women’s rights and Indonesia’s correctional system, focusing on the legal and social dynamics affecting incarcerated women. The study critically examines the Indonesian Correctional Act and its provisions related to women, highlighting the challenges of female inmates within a predominantly male-dominated penal system. While the act sets out various measures for the protection of women in detention, including separate facilities and gender-sensitive policies, its implementation often falls short, leaving women vulnerable to abuse, inadequate healthcare, and limited rehabilitation opportunities. The paper investigates how these gaps reflect broader societal attitudes toward women, where gender-based inequalities persist even within the criminal justice system. By analyzing legal texts, institutional practices, and interviews with legal experts and women prisoners, the research aims to provide a nuanced understanding of the challenges facing incarcerated women in Indonesia. It further discusses the role of state institutions, civil society, and international organizations in advocating for reforms that uphold women’s dignity and human rights in detention. Ultimately, the paper argues for a more comprehensive and gender-sensitive approach to prison reform, one that goes beyond the basic separation of male and female prisoners. It calls for the integration of policies that address the specific needs of women, such as maternal care, trauma-informed treatment, and vocational training, to ensure their rehabilitation and successful reintegration into society post-incarceration. This discourse serves as a critical step toward achieving a more equitable and humane correctional system for women in Indonesia.